Tindak Tutur Direktif Pada Film Gundala Karya Joko Anwar - Diaz Parama Arta; Mualafina Rawinda Fitrotul; Azzah Nayla (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2023)
The study which is based on the instructive statement in the film "Gundala" by Joko Anwar seems to focus on the analysis of directive speech acts. Tells the journey of an orphan named Sancaka who later becomes a superhero. In the analysis of directive speech acts, imi studies explain the form and function of these speech acts in the context of the film. Qualitative descriptive research method. The data collection technique used is free and interesting listening, which may refer to observation and analysis of dialogue texts in films. The results of this study seem to have identified forms of directive speech acts that exist in the film "Gundala," including ordering, advising, requesting, inviting, criticizing, and prohibiting. Apart from that, this study also tries to explain the various functions of directive speech acts, such as commands, requests, forcing, advice, suggestions, prohibitions, blocking, inviting, requesting, and reprimanding.